2019
DOI: 10.4317/jced.55840
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic re-treatment and restorative treatment of a dens invaginatus type II through new technologies

Abstract: Background The complex anatomy of dens invaginatus makes access cavity to root canal system difficult, which has an impact on the prognosis of these teeth. A novel technique, based on new technologies, is proposed to make access cavity conservative and guided with minimal dental structure lost. Material and Methods This case report shows the root canal retreatment and the endodontic surgery of a dens invaginatus type II in a left lateral upper incisor previously treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
9
0
2
Order By: Relevance
“…Zubizarreta et al also reported statistical significant differences ( p ˂ 0.05) between the endodontic access cavities planned and performed by computer-aided static navigation techniques with respect to freehand endodontic access cavities at coronal, apical, and angular deviations [ 10 ]. In addition, many authors have used computer-aided static navigation procedures to perform the endodontic access cavity in calcific metamorphosis cases [ 26 , 27 , 28 ] or dental malformations as dens invaginatus [ 29 , 30 ] or dens evaginatus [ 31 ]. Furthermore, computer-aided static navigation techniques have also been used to remove prosthetic fiber post into the root canal system [ 32 , 33 ] and guide prosthetic dental crown preparations [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zubizarreta et al also reported statistical significant differences ( p ˂ 0.05) between the endodontic access cavities planned and performed by computer-aided static navigation techniques with respect to freehand endodontic access cavities at coronal, apical, and angular deviations [ 10 ]. In addition, many authors have used computer-aided static navigation procedures to perform the endodontic access cavity in calcific metamorphosis cases [ 26 , 27 , 28 ] or dental malformations as dens invaginatus [ 29 , 30 ] or dens evaginatus [ 31 ]. Furthermore, computer-aided static navigation techniques have also been used to remove prosthetic fiber post into the root canal system [ 32 , 33 ] and guide prosthetic dental crown preparations [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…3,5,8,[12][13][14][15] Outro benefício promovido pela Endodontia guiada é uma nova forma de se abordar dentes com invaginação ou com evaginação. 6,7,10 Estas malformações dentárias dificultam o sucesso da terapia endodôntica visto que a instrumentação e desinfecção dos canais é mais complexa em virtude da alteração anatômica. Com o uso do endoguide, tornou-se possível acessar essa interface radicular de forma mais prática, assegurando um tratamento satisfatório e eficaz.…”
Section: Discussionunclassified
“…Com o uso do endoguide, tornou-se possível acessar essa interface radicular de forma mais prática, assegurando um tratamento satisfatório e eficaz. 7,10,18 Quando um paciente possui um pino de fibra de vidro insatisfatório, associado a lesão periapical e que requeira remoção, o endoguide pode ser utilizado. Como estes retentores intrarradiculares apresentam adesão à dentina, alto grau de resistência e cor semelhante à dentina, sua remoção pode se tornar bastante difícil, podendo ocorrer danos à estrutura dental.…”
Section: Discussionunclassified
“…Other case reports and one case series have also shown the feasibility and reliability of GET in cases with apical periodontitis as a late complication of dental trauma [ 23 31 ]. To our knowledge, there is currently only one guided endodontics case report, which describes a promising 18-month outcome of a dens invaginatus malformation case treated, followed by endodontic surgery and root-end filling with mineral trioxide aggregate [ 30 ].…”
Section: Introductionmentioning
confidence: 99%